Acoustic telemetry provides insights for improving conservation and management at a spawning aggregation site of the endangered Nassau grouper (Epinephelus striatus) - Nemeth, Richard S.; Kadison, Elizabeth; Jossart, Jonathan; Shivji, Mahmood; Wetherbee, Bradley M.; Matley, Jordan K. (Frontiers in Marine Science, 2023)
Nassau grouper (Epinephelus striatus, Serranidae) were one of the most important fishery species in the Caribbean, but are now listed as critically endangered. Population collapse in most places occurred primarily by fishers targeting their spawning aggregation sites, where thousands of fish gathered during full moon periods from December to April. Identifying management options for protecting this vulnerable period is crucial for their survival. In the US Virgin Islands, we tagged 24 Nassau grouper with acoustic transmitters at a fish spawning aggregation (FSA) site called the Grammanik Bank, a 1.5 km2, marine protected area (MPA) closed each year from February to April. We tracked their movements over a seven-year period and found that the small MPA protected Nassau grouper only 65% of time during the spawning season. Nassau grouper arrived at the FSA from January to May, with a peak in March, and made daily roundtrip migrations (1-25 km) from the FSA site. Females swam twice as far as males, while males were more sedentary and remained longer (22 d) at the FSA than females (9 d); behavioural characteristics that may cause differential bycatch mortality among sexes. We also found nearly half of all fish were temporary residents within 5 km of the FSA site for 2 to 6 months after the spawning season. This mismatch of MPA size and timing of closed season provided the impetus for developing new guidelines for protection. The large acoustic array allowed us to calculate spatially relevant areas useful for conservation including courtship arena (1.2 km2), staging area (4.7 km2) and primary migration pathways (9.6 km2) used by Nassau grouper during spawning season. To improve conservation goals of this endangered species, increasing the Grammanik Bank seasonal closure to five months and its size to 6.4 km2 would increase protection to >96%. These spatial and temporal changes to existing management regulations incorporate the best available data to improve conservation goals by reducing potential bycatch mortality, eliminating disturbance of spawning fish, and protecting critical spawning habitat for Nassau grouper. These guidelines may also be applied more broadly to other Nassau grouper FSA sites located on large insular or continental shelfs areas throughout the Caribbean.